Evaluasi manfaat penggantian chemical amine N1800 menjadi N1805 dalam rangka pengurangan jejak karbon - Wahyu Widiyantara; Muhammad Kurniawan Adiputra; Eka Wijayanto; Lisendra Marbelia (Jurnal Rekayasa Proses, 2021)
Continuous innovation in tools and/or processes in the chemical industry to achieve efficiency and an environmentally friendly industry is mandatory. In supporting this, PT. KMI modified the process by replacing the neutralizing amine material used in the boiler feed water system. The replacement of amine was carried out in mid-2017, from amine N1800 to N1805. Data on consumption of amines and solvent water for 2015-2020 was used as the basis for the evaluation. Estimation of the amount of emissions was also carried out by calculating the need for solvent water, drum containers for amine materials and also transportation of materials from the producer to PT. KMI. From the calculation results, it can be concluded that changing the amine material from N1800 to N1805 provides good benefits, namely: (1) reducing the annual cost of consuming amine, (2) reducing the need for solvent water and the burden of water pollutants and (3) reducing emissions significantly . The reduction in emissions mostly comes from savings in the use of container drums and transportation, while the reduction in water use is less significant.